2010
DOI: 10.1007/s10511-010-9129-6
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and photometric observations of TT Ari. III.

Abstract: The nova-like cataclysmic variable (CV) TT Ari was detected in its second deep minimum inNovember 2009. Study of its evolutionary phase is very important for research on the nature of CVs in the VY Scl group. During this phase the spectral energy distribution of the star changed rapidly. The emission lines of elements with high excitation, such as HeII λ4686 and NIII/CIII, as well as broad absorption in the hydrogen Balmer series, originating in the photosphere of the white dwarf or in the lower layers of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Cowley et al (1975) subsequently confirmed it as a CV through time-resolved spectroscopic observations. TT Ari is notable for displaying a wide range of variability on short timescales (e.g., Smak & St epień 1969;Mardirossian et al 1980), bright and faint state transitions (i.e., VY Scl behavior-see Appendix A.9; e.g., Gänsicke et al 1999;Kraicheva et al 1999;Melikian et al 2010), and both positive and negative superhumps (at different times). Emission line P Cygni profiles have been observed in its UV and optical spectra, likely indicative of an outflowing accretion disk wind (Melikian & Karapetian 2004;Hutchings & Cowley 2007).…”
Section: A5 Tt Arimentioning
confidence: 99%
“…Cowley et al (1975) subsequently confirmed it as a CV through time-resolved spectroscopic observations. TT Ari is notable for displaying a wide range of variability on short timescales (e.g., Smak & St epień 1969;Mardirossian et al 1980), bright and faint state transitions (i.e., VY Scl behavior-see Appendix A.9; e.g., Gänsicke et al 1999;Kraicheva et al 1999;Melikian et al 2010), and both positive and negative superhumps (at different times). Emission line P Cygni profiles have been observed in its UV and optical spectra, likely indicative of an outflowing accretion disk wind (Melikian & Karapetian 2004;Hutchings & Cowley 2007).…”
Section: A5 Tt Arimentioning
confidence: 99%
“…The first one was treated in some detail by Shafter et al (1985) and later by Gänsicke et al (1999), while Hutchings & Cote (1985) presented some complementary observations. To my knowledge, the only paper discussing observations of the 2009 -2011 low state was published by Melikian et al (2010). Apart from some time resolved light curves observed by Shafter et al (1985) not much detailed photometry performed in this state has been studied.…”
Section: The 2009 -2011 Low Statementioning
confidence: 99%
“…14, individual flares are heavily structured. Melikian et al (2010) have already drawn attention to this flaring activity of TT Ari during the low state. However, their limited amount of data did not permit a more thorough characterization of this behaviour.…”
Section: Intermittent Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cowley et al (1975) subsequently confirmed it as a CV through time-resolved spectroscopic observations. TT Ari is notable for displaying a wide range of variability on short timescales (e.g., Smak & Stȩpień 1969;Mardirossian et al 1980), bright and faint state transitions (i.e., VY Scl behaviorsee Section A.9; e.g., Gänsicke et al 1999;Kraicheva et al 1999;Melikian et al 2010), and both positive and negative superhumps (at different times). Emission line P Cygni profiles have been observed in its UV and optical spectra, likely indicative of an outflowing accretion disk wind (Melikian & Karapetian 2004;Hutchings & Cowley 2007).…”
Section: A4 Rw Sexmentioning
confidence: 99%